Synthesis, Antitubercular and Leishmanicidal Evaluation of Resveratrol Analogues - Coimbra, Elaine S.; Santos, Juliana A.; Lima, Larissa L.; Machado, Patricia A.; Campos, Debora L. [UNESP]; Pavan, Fernando R. [UNESP]; Silva, Adilson D. (Soc Brasileira Quimica, 2016)
In this paper we continue our efforts in the search for new Schiff bases as resveratrol analogues as promising antitubercular and antileishmanial agents. Compounds were evaluated in vitro against Mycobacterium tuberculosis and Leishmania species. Compounds showed varying activity against promastigotes of all Leishmania species tested (concentration leading to reduction of 50% of parasite growth-IC50 values ranging from 1.60 to 15.53 mu g mL(-1)). Majority of compounds exhibited good results against Leishmania species with IC50 values below 10.00 mu g mL(-1), with no cytotoxicity against macrophages. One of the analogues showed the best activity against amastigotes of L. amazonensis (IC50 = 5.73 mu g mL(-1)). Furthermore, the compounds showed comparable or better effect than drugs commonly used in tuberculosis treatment such as Cycloserine (R). The analogue that was the most active for M. tuberculosis had minimal inhibitory concentration MIC90=0.78 mu gmL(-1). The in vitro cytotoxicity on Vero cells (CC50), as well as the selectivity index (SI = CC50/MIC) were also evaluated, and showed that the synthesized analogues are not cytotoxic.
Keywords: resveratrol analogue; antitubercular evaluation; leishmanicidal evaluation; Schiff base; imine